A Review of Inside the Outbreaks: The Elite Medical Detectives of the Epidemic Intelligence Service<source>Inside the Outbreaks: The Elite Medical Detectives of the Epidemic Intelligence Serivce</source>; <person-group> <name name-style="western"> <surname>Pendergrast</surname> <given-names>Mark</given-names> </name> </person-group>; ( <year>2010</year>). <publisher-name>Houghton Mifflin Harcourt</publisher-name>. <publisher-loc>Boston</publisher-loc>. <fpage>432</fpage> pages. - Tara C. Smith (American Society for Microbiology, 2010)
Review of: Inside the Outbreaks: The Elite Medical Detectives of the Epidemic Intelligence Serivce ; Mark Pendergrast; (2010). Hough-ton Mifflin Harcourt. Boston. 432 pages.